Management of Avulsive Soft Tissue Ballistic Facial Injuries - Ding, Yang; Owens, Winston R.; Quirarte, Diego M.; Leonovicz, Olivia G.; Latham, Kerry P. (Seminars in Plastic Surgery, 2025)
Ballistic facial injuries are rare yet challenging cases for plastic surgeons that often comprise of avulsive tissue loss. They require in-depth assessment and staged reconstruction after patient stabilization. Each anatomic region of the face holds specific considerations that should be prioritized during reconstruction. Soft tissue repair techniques of facial gunshot wounds are widely variable and range from primary closure to multistage free flaps. Large, devastating facial defects after ballistic trauma previously posed significant challenges for reconstruction; however, advances in composite tissue transplant and allografts have expanded plastic surgeons' reconstructive arsenals. The goal of this review is to focus on the fundamentals of soft tissue management and reconstruction after ballistic facial injury. Through sound surgical principles, patients may achieve optimal aesthetic and functional outcomes despite experiencing highly morbid facial ballistic injuries.
Keywords: ballistic facial injuries; craniofacial trauma; soft tissue reconstruction; composite transplantation